Study on Void Structure Reconstruction of Asphalt Mixture by X-Ray Computed Tomography and Otsu’s Method - Jiantong Zhang; Jun Yang; Tiejun Liu; Rongxing Cai; Rui Yang (Advances in Materials Science and Engineering)
The purpose of this paper is to obtain the pore distribution of asphalt mixture accurately by nondestructive technology. Specimens prepared with four gradations of asphalt mixtures were scanned using X-ray computed tomography (CT) which was used to measure air void sizes at different depths within specimens. The air void distributions of obtained CT images were analyzed using ring blocking segmentation combining Otsu’s method, which provided an accurate estimate of air voids in asphalt mixtures. The image processing results showed that air void distribution was not uniform in the specimens; higher air void concentrations were found at the top and bottom of the specimen, and lower, in the rest of the sample depth. The air void sizes of SUP13 and AC13 are mainly distributed between 0.15 to 0.2 mm, while PA13 and SMA13 are 0.4 to 0.65 mm and 0.4 to 0.7 mm, respectively. It is believed that the CT pictures processed by the ring blocking segmentation combining Otsu’s method is feasible and rational to capture the air voids size and content of asphalt mixtures.+